Free space optic communications – a review of quality parameters - Alma, Husagic; Al-Khateeb, Wajdi Fawzi Mohammed (IIUM Press, 2011)
The optical telecommunications have paved the way for a massive expansion in global telecommunications networks over the past few decades. There has been a tremendous explosion in bandwidth demand and requirements. For the end user to access and utilize the broad array of services made available through these developments, network designers must provide a flexible and cost-effective solution for the "last mile" between the LANs, MANs, or WANs. High bandwidth, rapid installation, higher security, and non-binding accessibility are some of the features that describe Free Space Optical (FSO) Technology. As such, FSO would be able and solve many problems faced by today's traditional wireless communications, from security, bandwidth limitations to last mile problem. Considering that FSO Technology uses optical signals, the performance of FSO links happen to be highly dependent on weather conditions more than microwave radio links